HydroMoth: Testing a prototype low‐cost acoustic recorder for aquatic environments. Issue 3 (4th January 2022) - Lamont, Timothy A. C.; Chapuis, Lucille; Williams, Ben; Dines, Sasha; Gridley, Tess; Frainer, Guilherme; Fearey, Jack; Maulana, Permas B.; Prasetya, Mochyudho E.; Jompa, Jamaluddin; Smith, David J.; Simpson, Stephen D.
Abstract: Passive acoustic monitoring (PAM) involves recording the sounds of animals and environments for research and conservation. PAM is used in a range of contexts across terrestrial, marine and freshwater environments. However, financial constraints limit applications within aquatic environments; these costs include the high cost of submersible acoustic recorders. We quantify this financial constraint using a systematic literature review of all ecoacoustic studies published in 2020, demonstrating that commercially available autonomous underwater recording units are, on average, five times more expensive than their terrestrial equivalents. This pattern is more extreme at the low end of the price range; the cheapest available aquatic autonomous units are over 40 times more expensive than their terrestrial counterparts. Following this, we test a prototype low‐cost, low‐specification aquatic recorder called the 'HydroMoth': this device is a modified version of a widely used terrestrial recorder (AudioMoth), altered to include a waterproof case and customisable gain settings suitable for a range of aquatic applications. We test the performance of the HydroMoth in both aquaria and field conditions, recording artificial and natural sounds, and comparing outputs with identical recordings taken with commercially available hydrophones. Although the signal‐to‐noise ratio and the recording quality of HydroMoths are lower than commercially available hydrophones, the recordings with HydroMoths still allow for the identification of different fish and marine mammal species, as well as the calculation of ecoacoustic indices for ecosystem monitoring. Finally, we outline the potential applications of low‐cost, low‐specification underwater sound recorders for bioacoustic studies, discuss their likely limitations, and present important considerations of which users should be aware. Several performance limitations and a lack of professional technical support mean that low‐cost devices cannot meet the requirements of all PAM applications. Despite these limitations, however, HydroMoth facilitates underwater recording at a fraction of the price of existing hydrophones, creating exciting potential for diverse involvement in aquatic bioacoustics worldwide. Abstract : In this paper, we demonstrate the current lack of commercially available low‐cost aquatic sound recorders. We then test a prototype device that is twenty times cheaper than currently available hydrophones. Technology like this will open up the field of aquatic bioacoustics to people and organisations who have never before been able to listen underwater.